How Well Are Socioeconomic Factors Associated With Improved Outcomes for Infants Diagnosed With Early Childhood Developmental Delay? An Observational Study - Ji, Fang; Sun, Yao; Xu, Yi; Tang, Jian; Hu, Jing (Frontiers in Pediatrics, 2022)
Purpose: Early childhood developmental delay remains problematic around the world in terms of weight, gross motor, fine motor, cognitive, language, and social domains. Based on the WHO guideline and the Theoretical Domains Framework, this study identified five key socioeconomic factors, including parenting time during hospitalisation, parent’s educational level, medical spending, distance to hospital, and medical insurance coverage, to describe how these five factors are associated with the improved outcomes of infants’ developmental quotient values and weight in a tertiary hospital. Methods: In this prospective observational study, both clinical and socioeconomic data were collected. The clinical data includes infants’ weight, developmental quotient values, and other data relevant to infants’ birth. A National Developmental Scale was used to observe infants over five domains and calculate infants’ developmental quotient values. These five domains include gross motor, fine motor, cognitive, language, and social domains. Parenting time during hospitalisations was observed by a research nurse. Other socioeconomic factors were reported by parents and verified with information in the system. Results: A total 75 infants’ parents were approached, with 60 recruited. Infants’ age ranged from 75 days to 274 days at first admission. The increments of their weight and the developmental quotient values were improved ranging from -0.5kg to 2.5kg and from -13 to 63 respectively. Over half of parents (54.1%) were at level of minimum secondary education, although the results were statistically non-significant. However, there were positive correlation between the improved weight and parenting time during hospitalisation (r (58)= .258, p < .05), medical spending (r (58)= .327, p < .05), distance to hospital (r (58)= .340, p < .01), but negatively associated with medical insurance coverage (r (58)= - .256, p < .05). There was also significant relationship between the improved developmental quotient value and distance to hospital (r (58)= .424, p < .01). Conclusion: Parenting time during hospitalisation, medical spending, distance to hospital and medical insurance coverage are important factors for early childhood developmental delay in relation to possible hospital intervention and improved accessibility to health services for families in rural area. Current medical subsidy scheme change is necessary.